Implementation of Prophetic Leadership Values : in Business Organizations - Darmawan, Didit; Evadiana, Mareta Sari; Putri, Salsabila Arneta Setiana; Dardiyanti, Erinda Salsabila; Abdurrahman, Bagas (Al-Iqtishadiah: Jurnal Hukum Ekonomi Syariah, 2026)
The modern business world requires a leadership model that is not only profit-oriented but also able to address ethical and moral challenges. Prophetic leadership emerged as a concept that integrates spiritual and managerial values ​​to create a character-driven organization. This study aims to examine the development of the concept of prophetic leadership in management literature and analyze its impact on the formation of organizational culture. The method used is a literature study by examining various relevant scientific theories and concepts. The results of the study indicate that this concept has developed rapidly and offers leadership characteristics based on truth, justice, and exemplary behavior. The application of these values ​​can shape a humanistic, transparent, and productive organizational culture, which ultimately improves the overall performance and sustainability of the organization.